Answer:
They each get 8 cookies
Step-by-step explanation:
24 divided by 3 is 8. There are other ways if the question allows there to. be some cookies left over.
Given that median area is 15 square units.
Hence rectangle C in the middle has 15 square units.
Its dimensions can be width= 5 and length = 3
SInce B is smaller than C and has the same length, B has lengh of 3 with area = 9 sq units.
D has the same perimeter = 16 units. Since D is a square, side of D = 4 units.
Now D and E have the same length. Hence length of E = 4 units.
Width of E = width of C = 5 units.Thus makes the area of E as 20 sq units.
Rectangle A has length =3 and width can be less than 3 since area is smaller than B.
so A has length= 3 width = 2 with area = 6 sq units.
Answer:Slope is 3 y-intercept is -2
Step-by-step explanation:
y=mx+b. m=slope b is y-intercept
y=3x-2
Comparing both equations we find out that slope is 3 and y-intercept is -2
Step-by-step explanation:
Answers : A and D
Step - by - step explanation :
tip : when finding constant of proportionality it's always Y divided by X
A = what is 22.5 divided by 3 ? 7.5 ( now multiply 7.5 by the next X [ 4 ] )
what is 7.5 x 4 ? 30 ( and since on the graph it also says 30 then you can assume this one has a proportional relationship )
B = what is 12 divided by 3 ? 4 ( now multiply 4 by the next X [ 5 ] )
what is 4 x 5 ? 20 ( and because the graph says 25 then you know it's NOT a proportional relationship )
C = what is 8.5 divided by 2 ? 4.25 ( now multiply 4.25 by the next X [ 5 ] )
what is 4.25 x 5 ? 21.25 ( and because the graph says 22.5 then you know it's NOT a proportional relationship )
D = what is 10 divided by 2 ? 5 ( now multiply 5 by the next X [ 3 ] )
what is 5 x 3 ? 15 ( and since on the graph it also says 15 then you can assume this one has a proportional relationship )
( sorry it took me so long to write this )
So the question is asking: (x-4)(x-2)
because there is a bracket in between the two expressions it means we have to multiply them together: (x-4) x (x-2)
you can break down the question into smaller parts:
x multiply x
x multiply -2
-4 multiply x
-4 multiply -2
here are the answers:
x^2 (means x squared)
-2x
-4x
8 (because when you multiply two negative numbers it makes a positive)
now you put it into an expression (this is expanding):
x^2 - 2x - 4x + 8
to simplify it you collect like terms:
x^2 - 6x + 8
The above is the answer :)